Особливості призначення та проведення судових експертиз при розслідуванні злочинів терористичного характеру - Скуба, Г.; Skuba, G. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлюються питання призначення та проведення судових експертиз при розслідуванні злочинів терористичного характеру, проаналізовано види судових експертиз та їх значення. Автором присвячено увага новим для України видам судових експертиз – комплексній психолого-лінгвістичній та відеофонографічній. Виявлено новітні тенденції можливостей судових експертиз. Розслідування злочинів терористичного спрямування потребує використання спеціальних знань, новітніх методів та методик задля повного, всебічного та об’єктивного встановлення всіх обставин справи, що забезпечується широким спектром судових експертиз.In this article there are highlighted points of appointing and leading forensic enquiries at investigation terrorist crimes, analysed types of forensic expertises and their abilities. The autor payed attention to forensic expertises, which are new for Ukraine – complex psychological-linguistic and videographic forensic expertises. There were elicted new tendencies in using these forensic expertises. Determination of influence on aims and acts of some people and groups of people with the help of information, which is transmitted by terrorists before or after carrying out a terrorist act by mass media, Internet is one of the psychological-linguistic expertise task. There were made conclusions that forensic expertise results are ones of the most important and cogent arguments, that are used at the pre-trial investigation of terrorist acts. Investigation of terror crimes requires the usage of peculiar knowledge and modern methods for complete and objective setting out all circumstances of the court case, which provides with the wide range of forensic expertises.
Circumstances of Appointing and Leading Forensic Expertise at Investigation of Terrorist Acts
Keywords: експерт; судова експертиза; висновок експерта; терористичний акт; слідчий; досудове розслідування; речові докази; expert; forensic expertise; experts’ conclusion; terrorist act; investigator; pre-trial investigation; material evidence